2016
DOI: 10.3171/2015.5.spine141191
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic spinal subdural hematoma complicating anterior cervical discectomy and fusion: case report

Abstract: A spinal subdural hematoma is a rare clinical entity with considerable consequences without prompt diagnosis and treatment. Throughout the literature, there are limited accounts of spinal subdural hematoma formation following spinal surgery. This report is the first to describe the formation of a spinal subdural hematoma in the thoracic spine following surgery at the cervical level. A 53-year-old woman developed significant paraparesis several hours after anterior cervical discectomy and fusion of C5–6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We identified three prospective studies,[ 7 20 37 ] 13 retrospective studies,[ 10 27 28 29 32 33 34 35 37 40 65 74 75 ] and four case reports. [ 68 76 77 78 ] The case reports comprised one case of retropharyngeal hematoma 33 h after surgery presented with cervical swelling and dysphagia,[ 68 ] and one case of postoperative cervical hematoma complicated by ipsilateral carotid thrombosis and aphasia after anterior cervical fusion. [ 77 ] A case of cervical wound hematoma 6 weeks after 1-level ACDF was associated with instrument settling resulting in neck pain, dysphagia, and shortness of breath.…”
Section: Resultsmentioning
confidence: 99%
“…We identified three prospective studies,[ 7 20 37 ] 13 retrospective studies,[ 10 27 28 29 32 33 34 35 37 40 65 74 75 ] and four case reports. [ 68 76 77 78 ] The case reports comprised one case of retropharyngeal hematoma 33 h after surgery presented with cervical swelling and dysphagia,[ 68 ] and one case of postoperative cervical hematoma complicated by ipsilateral carotid thrombosis and aphasia after anterior cervical fusion. [ 77 ] A case of cervical wound hematoma 6 weeks after 1-level ACDF was associated with instrument settling resulting in neck pain, dysphagia, and shortness of breath.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the avoidance might be through partial resection and coagulation of the edges. Protzman et al [31] reported that extradural hematoma could complicate ACDF. They attributed it to local trauma at the operative site and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Following ACDF, 2 case studies documented how immediate returns to the operating room without postoperative MR scans failed to correctly diagnose the locations of postoperative hematomas [Table 1]. [7,18] In Hans et al (2003) study, 2.5 hours following a C67 ACDF, the patient developed acute flaccid quadriplegia; they immediately returned to the operating room without a repeat MR to remove a presumed anterior C67 PEH. [7] However, when they failed to find the clot, they then obtained a STAT MR that demonstrated a posterior PEH that warranted an immediate C3-T3 laminectomy.…”
Section: Two Case Studies Of Acute Returns To the Operating Room With...mentioning
confidence: 99%
“…In the second case (2016), following a C56 ACDF, the patient developed acute postoperative paraparesis; the immediate return to the operating room without an MR failed to reveal an anterior C56 PEH. [ 18 ] The patient subsequently underwent a STAT cervical/thoracic MR that demonstrated a thoracic subdural hematoma that was acutely treated with a thoracic laminectomy.…”
Section: Introductionmentioning
confidence: 99%